Closed Ended Structured Questionnaire in Fast Track Familiarization of Nurses to Conduct Telephone Follow-up after Open Carpal Tunnel Release - Hannula, Leevi (My University, 2021)
Background Open carpal tunnel release (OCTR) due to chronic carpal tunnel syndrome (CTS) is the most common procedure in hand surgery. CTS is often bilateral. A follow-up is required to detect any complications and confirm successful recovery before contralateral procedure is booked. Objectives The purpose of this study is to evaluate a closed ended questionnaire to assist nurses when starting routine follow-up telephone interviews after carpal tunnel surgery. Methods In our hospital routine follow-up phone calls to the patients 3 months after OCTR were allocated to nurse practitioners instead of surgeons. Once the practice was started a structured face validated closed ended questionnaire was used to collect data from a total of 61 consecutive patients. Results Nurse practitioners performed the follow-up independently in 97 % (59/61) of the cases. Ten per cent (6/61) of the patients were assigned further appointments to a surgeon and one patient was referred to an occupational therapist. 2 patients contacted the hospital after the telephone interview because of minor complaints. Patient charts were reviewed 18 months after the phone calls. No missed complications were detected. Conclusions We conclude that a structured closed ended questionnaire is useful assist in fast track familiarization of nurse practitioners for the follow-up contact after OCTR.
Keywords: Carpal tunnel release, Carpal tunnel syndrome, Hand surgery